Point-Of-Care Ultra-Sound (POCUS) for suspected surgical abdominal conditions in rural India-a mixed-method health needs assessment - Owen Thomas; Noel Aruparayil; Jesudian Gnanaraj; George Mathew; Kavikumar Nagarajan; Beth Shinkins; David Jayne (Public Library of Science (PLoS), 2023)
Introduction Evidence has shown a trend towards rising mortality from surgical abdominal conditions with increasing distance from hospitals in Eastern India. It has been claimed that imaging modalities such as portable ultrasound are ideal for use in rural areas of developing countries for diagnosis and management of a variety of acute abdominal conditions. This mixed-methods study aimed to explore the need for increased access to POCUS in rural, hard-to-reach populations within India, and to identify barriers that may exist to increasing this access. Methods This mixed-methods study utilized a health needs assessment framework. Quantitative data was extracted from medical records within two outreach camp organisations supporting hard-to-reach populations in Uttarakhand and Jharkhand to provide contextual background statistics. Qualitative data was collected using semi-structured interviews taken from employees of each outreach camp. A framework analysis was employed to analyse the qualitative data. Both datasets were analysed in parallel. Results Twelve semi-structured interviews were undertaken, and 3 months of medical records were reviewed. Themes that presented themselves from the data included the use of camps for case-finding of conditions amenable to routine surgery, a need for POCUS to help with this diagnostic process, a perceived high disease burden from renal calculi, and complex cultural and legislative barriers to POCUS specific to this setting. Discussion POCUS was considered a useful tool in expanding access to surgery for these settings and finding ways of overcoming cultural and legislative barriers to its use should be of high priority. POCUS should be highly portable, robust, easily repairable, and battery operated. For telemedicine to be fully utilised, signal quality will have to be proven to be reliable.